2013
DOI: 10.4049/jimmunol.1202677
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-22– and TNF-α–Producing Th22 Cells in Uveitis Patients with Behçet’s Disease

Abstract: Behçet’s disease is a systemic inflammatory disorder with recurrent episodes of oral ulceration, skin lesions, genital ulceration, and intraocular inflammation (uveitis). The intraocular inflammation is strictly associated with Th effector cells. IL-22 is a member of the IL-10 cytokine family that is involved in inflammatory processes. Recently, Th22 cells were identified as a Th cell population that produces IL-22 and TNF-α and are distinct from Th1, Th2, and Th17 cells. In this study, we established Th22-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 28 publications
3
49
0
2
Order By: Relevance
“…Behçet hastalığında aktif üveiti olan hastalarda oküler örnekler alınmış ve bu örneklerde yüksek miktarda İL-22 ve TNF-α olduğu saptanmış, ancak Th1 sitokini İFN-γ ve Th17 sitokini İL-17 normal olarak bulunmuş. Hastaların periferik kan örneklerinde ise in vitro olarak İL-6 ve TNF-α varlığında CD4 T hücrelerinin Th22 hücrelerine dönüştüğü görülmüş (17). Bu çalışmanın sonuçlarına göre, İL-22 ve TNF-α'nın Behçet hastalarında oküler immün cevapta bu sitokinlerin önemli rolü olduğu düşünülmüştür.…”
Section: Introductionunclassified
“…Behçet hastalığında aktif üveiti olan hastalarda oküler örnekler alınmış ve bu örneklerde yüksek miktarda İL-22 ve TNF-α olduğu saptanmış, ancak Th1 sitokini İFN-γ ve Th17 sitokini İL-17 normal olarak bulunmuş. Hastaların periferik kan örneklerinde ise in vitro olarak İL-6 ve TNF-α varlığında CD4 T hücrelerinin Th22 hücrelerine dönüştüğü görülmüş (17). Bu çalışmanın sonuçlarına göre, İL-22 ve TNF-α'nın Behçet hastalarında oküler immün cevapta bu sitokinlerin önemli rolü olduğu düşünülmüştür.…”
Section: Introductionunclassified
“…The Th22 cell line primarily secretes IL-22 and TNF-α and expresses CC chemokine receptor (CCR) 4, CCR6, and CCR10. Th22 cell develops along a pathway that is distinct from that of the Th1, Th2, or Th17 differentiation pathways [17,19]. To induce Th22 differentiation, IL-6 is a major effector, while it can also be promoted by TNF-α in the presence of IL-6.…”
Section: Mice and Iodine-induced Thyroiditismentioning
confidence: 99%
“…It was originally reported that Th22 cells were important in the pathogenesis of chronic inflammatory skin diseases [20,21]. Th22 cells have also been shown to contribute to numerous autoimmune diseases such as atopic dermatitis [22], Behcet's disease [19], systemic lupus erythematosus [23], rheumatoid arthritis [24], immune thrombocytopenia [25], systemic sclerosis [26], and others. Recently, it was reported that Th22 cells were elevated at the onset of GD [27] and in newly diagnosed HT patients [28].…”
Section: Mice and Iodine-induced Thyroiditismentioning
confidence: 99%
See 2 more Smart Citations